ANALISIS TENTANG RENDAHNYA MINAT BELAJAR PESERTA DIDIK KELAS XI SMA NEGERI 5 PONTIANAK - Marti in, Marti in; Wicaksono, Luhur; Purwanti, Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was about an analysis of low learning interest on eleven grade students of senior high school 5, Pontianak. The general problem in this study is how is the low learning interest on eleven grade students of senior high school 5, Pontianak? The sub-problems are (1) What are the characteristics of the low learning interest of students on eleven grade of senior high school 5, Pontianak? (2) What are the internal factors that cause the low learning interest of students on eleven grade of senior high school 5, Pontianak? (3) What are the external factors that cause low learning interest of students on eleven grade of senior high school 5, Pontianak? (4) What efforts have been made by the guidance and counseling teacher to overcome the low learning interest students on eleven grade of senior high school 5, Pontianak?. This study used descriptive method in form of survey. The research subjects were 32 eleven grade students. Indirect communication and questionnaire were used as technique and tool of data collections. The technique analysis used percentage. Based on, the students on eleven grade of senior high school 5 reached 85% of low learning interest and categorized as